2017
DOI: 10.1155/2017/2847303
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular Prostate-Specific Membrane Antigen Expression Is Associated with Improved Overall Survival under Palliative Chemotherapy in Patients with Pancreatic Ductal Adenocarcinoma

Abstract: Aims Expression of PSMA (prostate-specific membrane antigen) has been demonstrated in various cancers, including pancreatic ductal adenocarcinoma (PDAC). However, PSMA expression in PDAC-associated neovasculature has so far not been systematically analyzed. Methods and Results We analyzed PSMA expression in 81 PDAC tissue samples from 61 patients. Microvessel density (MVD) was assessed by software-based image analysis and showed a mean MVD of 63.7 microvessels/0.785 mm2. PSMA was practically absent in tumor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(31 reference statements)
2
9
1
Order By: Relevance
“…This study also found that higher levels of PSMA expression correlated with higher pathological stages III and IV . Another German study detected PSMA in almost two‐thirds of the cases of pancreatic ductal adenocarcinoma associated neovasculature . However as with many other solid tumours, PSMA was only expressed in a small proportion of actual pancreatic adenocarcinoma cells .…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…This study also found that higher levels of PSMA expression correlated with higher pathological stages III and IV . Another German study detected PSMA in almost two‐thirds of the cases of pancreatic ductal adenocarcinoma associated neovasculature . However as with many other solid tumours, PSMA was only expressed in a small proportion of actual pancreatic adenocarcinoma cells .…”
Section: Introductionsupporting
confidence: 69%
“…Another German study detected PSMA in almost two‐thirds of the cases of pancreatic ductal adenocarcinoma associated neovasculature . However as with many other solid tumours, PSMA was only expressed in a small proportion of actual pancreatic adenocarcinoma cells . Further studies are needed to determine if these findings can be utilized in the early detection and treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of PDAC TMAs has been described previously 71 . All tissue samples were collected for the purpose of histopathologic diagnosis and anonymised for the use in this study.…”
Section: Methodsmentioning
confidence: 99%
“…This was approved by the ethics committee of the University of Münster (Approval Number 2015-102-f-S). About 4 µM thick slides were cut and stained using anti-κB-Ras antibody (1:50 dilution) as previously described 71 . In brief, sections were deparaffinised in xylene and rehydrated through graded ethanol at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Prostate-specific membrane antigen (PSMA) is a cell membrane-associated enzyme, functioning as carboxypeptidase, thereby degrading protein or peptide bonds. PSMA is believed to be involved in induction of tumor neoangiogenesis; however, the exact mechanism remains unclear [ 119 ]. PSMA is expressed in 68% of the tumor-associated neovasculature in PDAC, and to a lesser extent on tumor cells, while no PSMA overexpression in healthy pancreatic tissue and pancreatitis is reported [ 119 , 120 , 121 ].…”
Section: Molecular Targets In Pancreatic Ductal Adenocarcinoma (Pdac)mentioning
confidence: 99%